TINJAUAN HERMENEUTIS TERHADAP HADIS KEPEMIMPINAN PEREMPUAN DALAM ISLAM - Wahyudi Wahyudi; Nur Fadilah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
This paper discusses the hermeneutical perspective of the prohibition for women to become leaders hadith narrated by Abu Bakrah. The factor that became the background of this study is that there are still many people who understand that women are the second creature, namely